2020
DOI: 10.1021/acsomega.0c03320
|View full text |Cite
|
Sign up to set email alerts
|

Design of Potential Pharmaceutical-Based Metal Complexes Derived from Cromolyn a Mast Cell Stabilizer

Abstract: A series of pharmaceutical metal complexes (pMCs) were produced and characterized using the mast cell stabilizer, cromolyn, and bioactive metal ions (Zn +2 , Mg +2 , and Ca +2 ). Three novel pMCs, Cromolyn-Zn, Cromolyn-Mg, and Cromolyn-Ca, were formed through reactions under controlled temperature and pH conditions. Additional characterization for these materials was performed employing a number of solid-state characterization techniques, such as thermogravimetric analysis (TGA), powder and single-crystal X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…cultured mast cells. Despite this, earlier research on the pharmacological actions of CS demonstrated its ability to inhibit mediator release through mast cells (5). This agent was found to enhance healing and reduce inflammatory responses in the nose, trachea, and lungs by modulating the expression of IL-6, TNF-α, TLR3, and TRIF in a rat model of influenza (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cultured mast cells. Despite this, earlier research on the pharmacological actions of CS demonstrated its ability to inhibit mediator release through mast cells (5). This agent was found to enhance healing and reduce inflammatory responses in the nose, trachea, and lungs by modulating the expression of IL-6, TNF-α, TLR3, and TRIF in a rat model of influenza (30).…”
Section: Resultsmentioning
confidence: 99%
“…Originally developed for allergic asthma, it has shown potential in managing mastocytosis, allergic skin diseases, and intestinal allergies. Previous research on CS's pharmaceutical effects has shown it suppresses mediators released from mast cells triggered by specific antigens, potentially reducing the activation of other cell types (5)(6)(7). Cromolyn is effective in treating asthma, systemic mastocytosis, aphthous ulcers, and food allergies (8).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, GPR35 mRNA is upregulated upon challenge with IgE antibodies [ 96 ], suggesting that GPR35 may be a potential target for using cromolyn sodium in the treatment of asthma. Previous studies on the pharmacological actions of cromolyn sodium indicate that it prevents the release of mediators from mast cells [ 126 ], although recent studies employing mouse [ 127 ] and human [ 128 ] cultured MCs questioned cromolyn sodium function as a MC stabilizer agent. Regardless, the mechanism of action for this agent has been noted as inhibiting the activity of protein kinase C and transport of chloride into MCs [ 97 ].…”
Section: Covid-19 Drug Therapiesmentioning
confidence: 99%
“…Cromolyn sodium works by inhibiting the histamine release from conjunctival mast cells and degranulating sensitized mast cells [5,6]. The biopharmaceutical classification system classifies Cromolyn sodium as a class III compound.…”
Section: Introductionmentioning
confidence: 99%